Dielectric and electrochemical properties of hybrid Pt nanoparticles deposited on reduced graphene oxide nanoparticles /poly (vinylidene fluoride) nanocomposites - Karaphun, Attaphol; Tuichai, Wattana; Chanlek, Narong; Sriwong, Chaval; Ruttanapun, Chesta (My University, 2021)
Nano-sized platinum (Pt) materials deposited on reduced Graphene Oxide (rGO) nanosheets (hybrid Pt-rGO nanoparticle) were prepared by the seed-mediated growing process using 20 wt% of Pt nanomaterials in rGO suspension. Dielectric properties of hybrid Pt-rGO nanoparticles/poly (vinylidene fluoride) nanocomposites (Pt-rGO/PVDF nanocomposites) were synthesized by a liquid–phase assisted dispersion and hot–pressing methods with different volume fractions (f) of hybrid Pt-rGO nanoparticle loading PVDF nanocomposites. The observed particle size of Pt nanomaterials deposits on rGO nanosheets was 5 nm. The dielectric constant (ε′) of Pt-rGO/PVDF nanocomposites was increased with increasing hybrid Pt-rGO nanoparticle. The volume fraction fPt-rGO ≈0.0786 exhibited excellent ε′ ≈ 86 with very low loss tangent (tanδ) ≈ 0.021 at 1 kHz. High dielectric properties of Pt-rGO/PVDF composite should be ascribed to combination of the micro-capacitor and Maxwell–Wagner–Sillars (MWS) effects. Electrochemical properties of speciﬁc capacitances (Csc) and capacity retention of hybrid Pt-rGO nanoparticle electrode were investigated by the cyclic voltammetry and the galvanostatic charge-discharge. Interestingly, the hybrid Pt-rGO nanoparticle electrode displayed maximum Csc value of 169.8 F g−1 at the current densities of 0.25 A g−1. This was due to the occurrence of various oxygen functional groups in the rGO- and Pt+ ions as contributing to form of pseudo-capacitance in hybrid Pt-rGO nanoparticle.
Keywords: Dielectric Constant; Electrochemical properties; Hybrid Pt-rGO nanoparticle; Poly vinylidene fluoride (PVDF); Pt nanoparticle-deposited rGO